Formulation and Antimicrobial Activity Evaluation of Liquid Soap Containing SCOBY (Symbiotic Culture of Bacteria and Yeast) and Kombucha from Tea and Lemongrass - Meta Yuliana; Novin Teristiandi; Aisya Tria Fitriani; Robiatul Adawiyah; Sonia Sonia; Aulia Juniarti (Sunan Kalijaga State Islamic University & Society for Indonesian Biodiversity, 2026)
Kombucha soap has the ability to inhibit pathogenic microbes. However, the production of soap, particularly kombucha liquid soap, has so far only utilized the kombucha broth. SCOBY, formed from the symbiosis of fungi and bacteria during kombucha fermentation, has potential health benefits, yet its application as an active ingredient in liquid soap has not been explored. This study aimed to formulate liquid soap containing SCOBY and kombucha as active ingredients and to evaluate its antibacterial and antifungal activities. Kombucha was prepared using two fermentation treatments: green tea fermentation (K1) and a combination of green tea with lemongrass decoction (K2). The resulting kombucha broth and SCOBY from each fermentation were used as active ingredients in liquid soap formulations with the following variations: 10% kombucha (K.K), 10% kombucha + 10% SCOBY (K.K+S), and 10% SCOBY (K.S). Each liquid soap was evaluated for its organoleptic properties, hedonic acceptance, antibacterial activity against Escherichia coli and Staphylococcus aureus, and antifungal activity against Candida albicans.The results showed that the best treatment was the liquid soap containing 10% kombucha + 10% SCOBY from green tea fermentation (K1), which exhibited inhibition zones of 1.75 mm against Staphylococcus aureus, 7 mm against Escherichia coli, and 6 mm against Candida albicans. In contrast, the liquid soaps containing 10% kombucha from green tea fermentation (K1) and the combination of green tea and lemongrass fermentation (K2) showed no inhibitory effect against Candida albicans. These findings indicate that the addition of SCOBY as an active ingredient can enhance the antimicrobial properties of liquid soap, particularly in inhibiting pathogenic fungi.